2018
DOI: 10.1177/1177271918782893
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Extractable Nuclear Autoantibodies in Wheat-Related Disorders

Abstract: Background and aims:There has been broad interest to explore the presence of autoimmunity among wheat-sensitive individuals, but neither the pathogenesis nor the relevance has been established. In this study, we evaluated the frequencies and levels of autoantibodies, which are important biomarkers of autoimmunity, in subjects with wheat-related disorders and controls. Anti-nuclear antibodies (ANA) and the specific ones against extractable nuclear antigens (ENA) were investigated.Methods:A total of 713 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…These chips are then placed on a 96-pillar plate and assayed against serum specimens to determine reactivity. The detailed fabrication information for the Wheat Zoomer is very similar to the one as reported in our previous work [9, 10].…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…These chips are then placed on a 96-pillar plate and assayed against serum specimens to determine reactivity. The detailed fabrication information for the Wheat Zoomer is very similar to the one as reported in our previous work [9, 10].…”
Section: Methodsmentioning
confidence: 80%
“…This peptide microarray-based assay tested serum specimens as an aid in diagnosis of celiac disease. The fabrication and validation of the peptide arrays are very similar to the manufacture procedures described in our previous work [9, 10]. In general, the immunoassay binding activities between the antibodies in the serum and the attached peptides were scanned by a fluorescence microarray scanner and the data were analyzed to differentiate the substantial levels of binding, which referred to the mean signal binding intensity of the subsequences.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, using our silicon-based microarray platform, IgG and IgA antibodies against gliadin epitopes were detected at 99% sensitivity and 100% speci city [8]. Our quest for understanding the role of food in different diseases led us to investigate the association of autoantibodies in wheat-related conditions wherein we found that a signi cant number of patients with wheat-related diseases had autoimmunity marked by the presence of anti-extractable nuclear antigens (ENA) autoantibody biomarkers [9]. Previous research indicated that rheumatoid arthritis (RA) patients who followed a 'gluten-free diet' experienced a signi cant reduction in disease activity [10].…”
Section: Introductionmentioning
confidence: 99%